Human-sized magnetic particle imaging for brain applications - M. Graeser (Nature Portfolio, 2019)
Magnetic particle imaging (MPI) has been applied to various pre-clinical settings, including detection of ischemic stroke in mice. Translation of MPI to a clinical setting has been obstacled by the lack of a device with sufficient bore size and, at the same time, reasonable technical requirements. Here the authors present a human-sized MPI device with low technical requirements designed for detection of brain ischemia.